QUESTION 4

4.1
Simplify, without using a calculator:
4.1.1
๐‘ ๐‘–๐‘› (โˆ’135ยฐ)ยท๐‘ ๐‘–๐‘› 240ยฐยท๐‘๐‘œ๐‘  25ยฐยท๐‘ก๐‘Ž๐‘› 480ยฐ /๐‘ ๐‘–๐‘› 115ยฐยท๐‘๐‘œ๐‘  135ยฐ
(7)
4.1.2
(2๐‘ ๐‘–๐‘›(270ยฐ+๐‘ฅ)+๐‘๐‘œ๐‘ (๐‘ฅโˆ’180ยฐ))ร— ๐‘ ๐‘–๐‘›๐‘ฅ 2๐‘๐‘œ๐‘  (90ยฐ+๐‘ฅ)+๐‘ ๐‘–๐‘› (180ยฐ+๐‘ฅ) ๐‘๐‘œ๐‘ ๐‘ฅ
(6)
4.1.3
๐‘๐‘œ๐‘  120ยฐ 3( ๐‘ ๐‘–๐‘› 45ยฐ ) 4 .2 ๐‘๐‘œ๐‘ 45ยฐ
(4)
4.2
Prove the identity: 1โˆ’๐‘ ๐‘–๐‘› ฮธ + 1โˆ’๐‘ ๐‘–๐‘› ฮธ = 2 1+๐‘ ๐‘–๐‘› ฮธ 1โˆ’๐‘ ๐‘–๐‘› ฮธ 1+๐‘ ๐‘–๐‘›ฮธ
(5)
4.3
Determine the general solution of ๐‘ก๐‘Ž๐‘› 2ฮธ =โˆ’ 2
(5)

1 answer

4.1.1
sin(-135ยฐ) = -sin(135ยฐ) = -sin(45ยฐ) = -โˆš2/2
sin(240ยฐ) = sin(60ยฐ) = โˆš3/2
cos(25ยฐ) = cos(25ยฐ)
tan(480ยฐ) = tan(120ยฐ) = -โˆš3
sin(115ยฐ) = sin(65ยฐ) = โˆš3/2
cos(135ยฐ) = -โˆš2/2

Therefore, the expression simplifies to:
(-โˆš2/2 * โˆš3/2 * cos(25ยฐ) * (-โˆš3)) / (โˆš3/2 * (-โˆš2/2))
= (-โˆš6/4 * cos(25ยฐ) * -โˆš3) / (-โˆš6/4)
= 3cos(25ยฐ)

4.1.2
Using trigonometric identities and simplifying, the expression becomes:
(2sin(x) + cos(x) - cos(x)) * sin(x) / (2cos(x) + 1) * cos(x)
= sin(x) * sin(x) / (2cos(x) + 1) * cos(x)
= sin^2(x) / (2cos(x)cos(x) + cos(x))
= sin^2(x) / (cos(2x) + cos(x))

4.1.3
cos(120ยฐ) = -1/2
sin(45ยฐ) = โˆš2/2
cos(45ยฐ) = โˆš2/2

Therefore, the expression simplifies to:
-1/2 * 3 * (โˆš2/2) / 4 * โˆš2/2
= -3/4

4.2
To prove the identity, we start with:
1 - sin(ฮธ) + 1 - sin(ฮธ) = 2 / (1 + sin(ฮธ)) * (1 - sin(ฮธ))

Expanding and simplifying both sides, we get:
2 - 2sin(ฮธ) = 2 - 2sin(ฮธ)

Therefore, the identity is proven.

4.3
To determine the general solution of tan(2ฮธ) = -2, we first find the reference angle:
tan(2ฮธ) = -2
2ฮธ = arctan(-2) + nฯ€
ฮธ = (arctan(-2) + nฯ€) / 2

Therefore, the general solution is:
ฮธ = (arctan(-2) + nฯ€) / 2, where n is an integer.